2016
DOI: 10.3389/fninf.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

PyRhO: A Multiscale Optogenetics Simulation Platform

Abstract: Optogenetics has become a key tool for understanding the function of neural circuits and controlling their behavior. An array of directly light driven opsins have been genetically isolated from several families of organisms, with a wide range of temporal and spectral properties. In order to characterize, understand and apply these opsins, we present an integrated suite of open-source, multi-scale computational tools called PyRhO. The purpose of developing PyRhO is three-fold: (i) to characterize new (and exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 68 publications
(80 reference statements)
1
58
0
Order By: Relevance
“…1B). 16,21 Here, the model simulates channel photocurrents characterized by two closed states (C1 and C2) and two open states (O1 and O2) using the following set of rate equations,…”
Section: Four-state Model Fittingmentioning
confidence: 99%
“…1B). 16,21 Here, the model simulates channel photocurrents characterized by two closed states (C1 and C2) and two open states (O1 and O2) using the following set of rate equations,…”
Section: Four-state Model Fittingmentioning
confidence: 99%
“…14). The model was designed in the direct lineage of similar work, carried out over the 337 past decade [11][12][13]27], but also taking into account the more recent conclusion on the 338 actual, more complex, photocycle of channelrhodopsins [25]. Additionally, our analysis 339 is based on a set of voltage-clamp experiments on ChrimsonR-transfected HEK293 cells 340 at a holding potential of −60 mV and at physiological temperature (for direct use in Direct observation of the data revealed that there is a fast light adaptation 347 mechanism that has not been described previously.…”
Section: On Time Constants Comparison 316mentioning
confidence: 99%
“…),(9),(10),(11),(12) and(13) display the comparison between the data and 295 the simulations for six different cells. They show that the main features are in fact 296 captured by the five-state model.297Activation curve 298…”
mentioning
confidence: 99%
“…Hence, computational modeling is fundamental to understanding the light-induced ionic transport in cell membranes, not only for cell physiology but also to develop new treatments. [34][35][36][37][38][39][40] Although the photoresponse of vf-Chrimson and vf-Chrimson-expressing neurons has only been recently experimentally studied, 10 it is also important to undertake a theoretical analysis to understand and optimize the photodynamics of this ultrafast red-shifted opsin.…”
Section: Introductionmentioning
confidence: 99%